2019
DOI: 10.1373/jalm.2018.027904
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Procalcitonin Assay on the Abbott Architect i1000

Abstract: Background Procalcitonin (PCT) is an emerging biomarker for detecting sepsis. Recently, the US Food and Drug Administration cleared the expanded use of this biomarker for guiding clinicians regarding antibiotic treatment. To our knowledge, there are no published method validations for the Abbott Architect PCT assay. This article will discuss the process of method validation of the B·R·A·H·M·S PCT assay on the Abbott Architect platform. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Increase in D-Dimer levels and abnormal D-dimer levels are associated with poor prognosis [34,35]. According to others authors, PCT and platelet count may be potential predictors of disease severity and PCT may be considered a secondary bacterial infection marker [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Increase in D-Dimer levels and abnormal D-dimer levels are associated with poor prognosis [34,35]. According to others authors, PCT and platelet count may be potential predictors of disease severity and PCT may be considered a secondary bacterial infection marker [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…We also note that the studies included in the present meta‐analysis report different assays to evaluate procalcitonin levels, which is also a limitation. However, we believe this is a minor limitation to our analysis, as studies have demonstrated concordance in procalcitonin levels across assays 41,42 …”
Section: Discussionmentioning
confidence: 99%
“…However, we believe this is a minor limitation to our analysis, as studies have demonstrated concordance in procalcitonin levels across assays. 41,42 Many studies were rated as good on the AHRQ standard. Several were poor, most commonly due to lack of comparability of cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is reported that the interference value determined for trimethoprim can exceed 10% (18). In another study comparing the methods of two different devices, it is stated that there may be high bias values in icteric serum samples ranging from 6.6% to 28.6% (19). This list is constantly expanding with similar new studies.…”
Section: Discussionmentioning
confidence: 99%
“…The drugs that have been found to typically increase or decrease serum PCT levels are drugs that cause an endogenous rise of cytokines (17,18). Also, it should be kept in mind that lipemic, icteric and hemolysis serums may cause problems such as low or excessive evaluation in laboratory results due to interference (18,19). Recent studies have demonstrated that there is an inverse correlation between vitamin D and PCT, that giving vitamin D to the patients or vitamin D deficiency in patients can significantly alter PCT results (20).…”
Section: Introductionmentioning
confidence: 99%